Arbitration under the Arbitration Act, 2001, Bangladesh: Procedural drawbacks and some plausible solutions (Dhaka University Law Journal, 2022)
In today’s world, parties in an agreement always want quick, costeffective and fair dispute resolutions mechanism. As an alternative form of dispute resolution, arbitration is considered one of the most common and binding methods of dispute resolution between parties. In the current age of global movement towards the promotion of foreign investment in Bangladesh and keeping pace with the international business and international commercial arbitration law, Bangladesh is not lagging behind any more. As a part of the Indian subcontinent, the practice of Arbitration in Bangladesh has been being observed in various forms since the time immemorial. Nonetheless, a new arbitration law named as ‘The Arbitration Act, 20011 was enacted consolidating both domestic and international commercial arbitration through repealing the British enacted ‘The Arbitration (Protocol and Convention) Act, 1937’, and ‘The Arbitration Act, 1940’.2 The new Act basically based on the Model Law on International Commercial Arbitration, 19853, which generates a single and unified legal system for arbitration in Bangladesh. However, the much wanted model arbitration law is not free from flaws and in some extent it fails to meeting up the expectations of the parties in agreement, who want the fast and easy access to justice. The main purpose of this paper is to examine the existing arbitration law and procedures in Bangladesh, what are the enabling and constraining factors for ensuring access to justice in the mentioned process, and how it can be used effectively to resolve the shortcomings in a rapidly evolving arbitration process where parties’ satisfaction is a key criterion.Dhaka University Law Journal, 2022, 33(1), 143-162